2022
DOI: 10.1007/s44187-022-00028-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbial quality and antimicrobial residue of local and industrial processed fruit juice sold in Tamale, Ghana

Abstract: Fruits are essential part of human nutrition that provides numerous health benefits. When processed into juice, they are either packaged and stored or consumed immediately. Some reports associate foodborne illness with consumption of natural beverages contaminated with pathogenic microbes. Also, concerns of antimicrobial resistance due to antimicrobial residues in fruit juices has been raised. Thus, this study assessed the microbial quality of fruit juice by determining the incidence and load of E. coli and Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…It could be attributed to high temperature involved in pasteurization which killed a lot of microbes present in carrot juice. This report was in agreement with the findings of Jimma et al 26 In addition, low temperature storage could also have contributed to reducing the microbial load of the carrot juices. Kaddumukasa et al 27 , reported a similar trend in a related study.…”
Section: Discussionsupporting
confidence: 93%
“…It could be attributed to high temperature involved in pasteurization which killed a lot of microbes present in carrot juice. This report was in agreement with the findings of Jimma et al 26 In addition, low temperature storage could also have contributed to reducing the microbial load of the carrot juices. Kaddumukasa et al 27 , reported a similar trend in a related study.…”
Section: Discussionsupporting
confidence: 93%
“…It was most detected in RTE vegetable salads, cabbage, lettuce, raw beef, raw chicken, raw goat meat, “Hausa koko”, “khebab,” as well as fresh and smoked fishes, with individual prevalence ranging from 2.1% to 100%. 23 - 41 , 44 , 46 , 48 , 50 - 55 , 57 , 60 - 62 , 64 - 67 , 69 , 74 , 75 , 77 - 83 The highest prevalence (100%) was recorded in lettuce and cabbage samples from a vegetable farm in Kumasi. 26 Staphylococcus spp.…”
Section: Resultsmentioning
confidence: 96%
“… 25 Salmonella spp. was reported by 32% (23/72) 23 - 25 , 28 , 29 , 31 , 35 , 36 , 38 , 44 , 50 , 51 , 53 , 58 , 60 , 66 , 74 , 76 , 78 , 80 - 83 from foods such as raw beef, chicken, chevon, salad, mixed spices, and locally produced fruit juices. The prevalence of Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short shelf life increases the risk of contamination of such a product by pathogenic microorganisms. Special attention is paid to freshly squeezed juices, since they do not undergo a pasteurization process and are infected with microbial pathogens more often than others [90,91]. The main pathogenic bacterial species polluting fruit juices include Escherichia coli, Listeria monocytogenes, Vibrio cholerae, Salmonella typhi, and Staphylococcus aureus, as well as members of the genera Shigella, Pseudomonas, and Alicyclobacillus (Figure 2C) [92,93].…”
Section: Microorganisms In Fruit Juicesmentioning
confidence: 99%